MULTIMEDIA TECHNOLOGIES IN AUDIOVISUAL ART - Sayyora Zakirova, (EPRA International Journal of Research and Development (IJRD), 2023)
This article discusses multimedia technologies in audiovisual art. The purpose of audiovisual creativity is to create an artistic image, which includes not only the image - the nature of the audiovisual work, but also the sound-visual image of the work, the image of each episode, scene, and everywhere figurativeness (visuality) turns into figurativeness.